Análisis de la evolución de los parámetros de calidad del aire en la construcción del puente nanay y viaductos de acceso 2018 - 2021, Punchana-Loreto – 2022 - Bacalla Neira, Hammer Joel (2023)
The study was carried out with the objective of analyzing the behavior of the environmental indices of the air in the work of the Nanay bridge, Bellavista, Punchana. Quantitative research of the observational, descriptive, analytical type. The secondary information was obtained from the Quarterly Monitoring Reports of the environmental air indices at the sampling points defined in the Nanay bridge work from 2018-2021, which were contrasted with the ECAs and the maximum permitted limits. It was found that the evolution of the parameters evaluated in the air: PM10, PM 2.5, Carbon Monoxide (CO), Sulfur Dioxide, Nitrogen Dioxide (NO2) and Hydrogen Sulfide (H2S) presented concentration levels well below the LMP as established in the ECA DS No. 003-2017-MINAM. Despite the fact that all the concentration levels of the parameters evaluated are below the environmental quality standards for air, in some specific quarters, the levels of the parameters increased slightly, when there was an increase in activities with the intensive use of heavy machinery coupled with tropical summer, but never exceeded the maximum limits allowed, so the alternative hypothesis is accepted and the null hypothesis proposed in the study is rejected.